Grass Carp Reovirus (GCRV) Giving Its All to Suppress IFN Production by Countering MAVS Signaling Transduction - Lu, Long-Feng; Li, Zhuo-Cong; Zhang, Can; Zhou, Xiao-Yu; Zhou, Yu; Jiang, Jing-Yu; Chen, Dan-Dan; Li, Shun; Zhang, Yong-An (Frontiers in Immunology, 2020)
Viruses typically target host RIG-I-like receptors (RLRs), a group of key factors involved in interferon (IFN) production, to enhance viral infection. To date, though immune evasion methods to contradict IFN production have been characterized for a series of terrestrial viruses, the strategies employed by fish viruses remain unclear. Here, we report that all grass carp reovirus (GCRV) proteins encoded by segments S1 to S11 suppress mitochondrial antiviral signaling protein (MAVS)-mediated IFN expression. First, the GCRV viral proteins blunted the MAVS-induced expression of IFN, and impair MAVS antiviral capacity significantly. Interestingly, subsequent co-immunoprecipitation experiments demonstrated that all GCRV viral proteins interacted with several RLR cascades, especially with TANK-binding kinase 1 (TBK1) which was the downstream factor of MAVS. To further illustrate the mechanisms of these interactions between GCRV viral proteins and host RLRs, two of the viral proteins, NS79 (S4) and VP3 (S3), were selected as representative proteins for two distinguished mechanisms. The obtained data demonstrated that NS79 was phosphorylated by gcTBK1, leading to the reduction of host substrate gcIRF3/7 phosphorylation. On the other hand, VP3 degraded gcMAVS and the degradation was significantly reversed by 3-MA. The biological effects of both NS79 and VP3 were consistently found to be related to the suppression of IFN expression and the promotion of viral evasion. Our findings shed light on the special evasion mechanism utilized by fish virus through IFN regulation, which might differ between fish and mammals.